The Influence of Car Rental Product Quality, Prices, and Complaint Handling System on Decisions to Use Car Rental Services at Botana Transport Rent Car & Tour Travel - Eko Prasetyo; Dhany Isnaeni Darmawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to determine the influence of product service quality, price, rental car complaint handling system on the decision to use car rental services at Botana Transport Rent Cars & Tours travel. This research was conducted at Botana Transport Rent Cars & Tours travel located on Jl. Raya Kemang, Cilegon City. The sample in this study consisted of 100 respondents using Accidental Sampling. The data analysis used is multiple linear regression. The results of the research are that product quality and the complaint handling system have a positive influence, while price has a negative influence on the decision to use a rental car at Botana Transport Rent. Cars & Tours travel. Simultaneously or at the same time, product quality, price and car rental handling system at Botana Transport Rent Cars & Tours travel. Meanwhile, the R Square value explains the decision to use car rental services at Botana Transport Rent Cars & Tours Travel is influenced by product quality, price and complaint handling system by 44.2% while the remaining 55.8% is influenced by other variables not used in this research.